The Effect of Financial Ratios on Stock Returns: By Mediation of Price Earning Ratio - Khan, Amar; Rahayu, Caecilia Wahyu Estining; Rahmawati, Christina Heti Tri (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study was conducted to analyze financial ratios effects towards Stock Returns in which the mediating variable is Price Earning Ratio (PER). The financial ratios are Debt to Equity Ratio (DER), Price to Book Value (PBV), and Return on Equity (ROE). This study uses a population of 65 real estate and property enterprises appeared in Indonesia Stock Exchange (IDX). This research’s samples are 36 companies registered in 2018-2020 IDX list. The data analysis technique uses Partial Least Square. The results showed (1) ROE and DER did not directly affect Stock Returns, (2) PBV directly affected Stock Returns, (3) ROE had an effect on Stock Returns partially mediated by the PER, (4) PBV and PER had no effect on Stock Returns mediated by the PER. The implications of the research result in investors needing to know the right time to make profitable investment decisions by analyzing the company's financial ratios to Stock Returns, which are an indicator of the level of profit earned by investors.